Mammalian diversity and conservation in the mixed-evergreen forest of Baraiyadhala national park, Chattogram, Bangladesh (Bangladesh Journal of Zoology, 2025)
The study was carried out to assess the mammalian diversity and conservation in Baraiyadhala National Park between October 2021 and June 2023 spanning a total of 78 field days. Field data were collected following a combination of different methods including transect walk, night survey, mist netting and camera trapping. Ten automated, infrared sensor camera traps were set up at 48 camera trap station for 14 months covering a total of 2793 camera days. Fifty-five species of mammals were recorded of which 41.82% was rare, followed by 29.09% common, 16.36% uncommon and 12.73% very common. Mammalian community of this national park were mostly nocturnal (32.73%), followed by metaturnal (23.64%), crepuscular (21.82%) and diurnal (21.82%). Overall mammalian diversity of this national park was very high (D = 0.06, H’ = 3.35). Among the recorded mammals, 17 species are threatened in different categories. Hunting and poaching with intentional forest fire were the major threats to the mammals of this national park.  Effective management plan involving local community, habitat restoration and introducing Spatial Monitoring and Reporting Tool (SMART) patrolling could minimize the threats to mammals in this national park.Bangladesh J. Zool. 52(3): 269-280, 2024